PENGARUH KEMAMPUAN PENGGUNA SISTEM INFORMASI, KETERLIBATAN PENGGUNA, DAN DUKUNGAN MANAJEMEN PUNCAK TERHADAP KINERJA SISTEM INFORMASI AKUNTANSI PADA PT BTPN AREA SURAKARTA - Muhammad Rofiq Sunarko, Shendy Cahyaning Utami, Dewi Saptantinah Puji Astuti & (Universitas Slamet Riyadi, 2016)
This study aims to (1) analyze the effect the ability of users of information systems to the performance of the accounting information system (2) analyze the effect of the involvement of users of information systems to the performance of accounting information system (3) analyze the effect on the performance of top management support information system of accounting. This study used a sample of 102 employees of PT BTPN area of Surakarta taken by area probability sampling. Collecting data using questionnaire techniques. Test requirements regression using classical assumption that multicolinearity test, autocorrelation test, heteroscedasticity test, and test for normality. Data were analyzed using multiple linear regression analysis. The conclusion of each hypothesis test results show that (1) The ability of users of information systems have a significant effect on the performance of accounting information system at PT Bank area of Surakarta, means that the hypothesis 1 is accepted; (2) Involvement of users of information systems has no significant effect on the performance of the accounting information system at PT Bank area of Surakarta, meaning hypothesis 2 is rejected (3) the support of top management have a significant effect on the performance of the accounting information system at PT Bank area of Surakarta, meaning third hypothesis is accepted.Keywords: capabilities of users information systems, involvement of users information systems, top management support, accounting information system performance.